17O-NMR spectroscopy to study the coordination of oxygen-based ligands to lanthanide ions in solution. Issue 9 (2nd May 2016) - Lin, Zhijin; Allen, Matthew J.
Abstract: The number of oxygen-based ligands coordinated to lanthanide ions influences the physical and chemical properties of lanthanide complexes, making this number important to study. We used peak shifts in 17 O-NMR spectroscopy to determine the number of individual nonhydroxyl-oxygen-based ligands coordinated to Dy 3+ . Oxygen-containing organic solvents were used as models to represent oxygen-based ligands to explore the scope of the technique because they contain a range of functional groups that have different electron-donating abilities and steric bulk. The measured coordination numbers of dimethylformamide, dimethyl sulfoxide, acetone, diethyl ether, tetrahydrofuran, di-isopropyl ketone, and hexamethyl acetone were consistent with reasonable values, indicating that 17 O-NMR spectroscopy is a useful technique to study the coordination chemistry of nonhydroxyl ligands to lanthanide ions in solution. Abstract :